The Determinants of South African Banks’ Capital Buffers - Sibindi, Athenia Bongani (Journal of Economics and Behavioral Studies, 2018)
The financing decisions of banks remain an enigma, increasingly attracting the attention of banking regulators and corporate finance scholars alike. The ‘buffer view’ of bank capital is premised on the notion that banks keep capital in excess of the regulatory requirements in line with bank specific factors. This study sought to test the ‘buffer view’ of bank capital. Utilising a sample of 16 South African banks for the period 2006-2015, panel data techniques were employed to estimate a fixed effects model to test the relationship between buffer capital and the firm level determinants of capital structure. It was established that the risk and size variables were negatively related to the buffer capital variable, whilst the dividend variable was positively related. This was consistent with the predictions of the buffer view of capital. The findings lend credence to the ‘buffer view’ school of thought about bank capital. These findings are also inconsistent with bank capital regulations solely determining the capital structures of banks but epitomises some measure of voluntary capital structure decision making by banking firms.